Impact of the People's Republic of China's growth slowdown on emerging Asia: A general equilibrium analysis - Fan Zhai; Peter Morgan (Asian Development Bank Institute (ADBI), 2016)
As an important global and regional economic power, the PRC's growth slowdown may cause large spillover effects to its neighboring economies. Using a multi-sectoral global computable general equilibrium model, this paper quantitatively investigates the impacts of a growth slowdown in the PRC for emerging Asian economies through trade linkages. The results suggest that a growth slowdown of 1.6 percentage points in the PRC would bring about a growth deceleration of 0.26 percentage points in developing Asia as a whole. However, the impacts vary dramatically by economy within developing Asia, reflecting their difference in economic and trade structure.
Keywords: C68; F44; F47; F62; 330; People's Republic of China; economic slowdown; spillover effects; emerging economies